Faktor-Faktor Kepuasan Pelanggan: Literature Review - Hengki Siswo Utomo; Mardani Mardani; Tubagus Regiasa Fajar (Amal Insani Foundation, 2023)
Previous or relevant research is fundamental in a study or scientific article. Prior or relevant research strengthens the theory and phenomenon of the relationship or influence between variables. This article reviews the factors that influence customer satisfaction in a study of the Marketing Management literature. The results of this literature review article are Service Quality affects Customer Satisfaction.